Psychometric properties of the Chinese version of the Get Active Questionnaire for Pregnancy and its companion form to assess physical activity readiness - Fangping Xu; Hua Tao; Zachary J. Weston; Liping Sun; Lingyan Lu; Xiaojiao Wang; Chunyi Gu (BMC Pregnancy and Childbirth)
Abstract Introduction Engaging in physical activity is essential for a healthy pregnancy. A reliable tool is necessary to enhance the assessment and counseling of safe physical activity. This study aimed to translate the original English Get Active Questionnaire for Pregnancy (GAQ-P) and its companion Health Care Provider Consultation Form for Prenatal Physical Activity (cHCP-CF-PPA) into simplified Chinese language and evaluate the psychometric properties in Chinese pregnant women. Methods The Brislin’s model of translation was employed to translate the GAQ-P/cHCP-CF-PPA tool. We conducted a cross-sectional study at a tertiary women’s hospital in Shanghai, China, enrolling a convenience sample of 325 pregnant women across all trimesters to evaluate the psychometric properties of the GAQ-P/cHCP-CF-PPA. Reliability was assessed through test-retest reliability and inter-rater reliability, while validity was examined using content validity, known-groups validity, and criterion validity. Sensitivity, specificity, positive predictive value, and negative predictive value were calculated using PARmed-X for Pregnancy as the gold standard. Results Regarding content validity, the GAQ-P had an average S-CVI/UA of 0.81 (I-CVIs: 0.83-1.0), while the cHCP-CF-PPA exhibited an average S-CVI/UA of 0.87 (I-CVIs: 0.83-1.0). The GAQ-P/cHCP-CF-PPA scores effectively distinguished women recommended for physical activity from those with contraindications. The Spearman’s correlations between the GAQ-P/cHCP-CF-PPA and the PARmed-X for Pregnancy were 0.851 for absolute contraindications and 0.847 for relative contraindications. The test-retest reliability score was 0.759 for physical activity contraindications, and 0.953 for inter-rater reliability. The sensitivity of the GAQ-P/cHCP-CF-PPA was determined to be 90.00%, with a specificity of 98.31%. The positive predictive value was 78.26%, while the negative predictive value reached 99.32%. Conclusion The Chinese version of the GAQ-P/cHCP-CF-PPA is a reliable and valid tool for assessing physical activity readiness in pregnant women.